1993
DOI: 10.1002/app.1993.070491003
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of olefins through heterogeneous catalysis. XIII. The influence of comonomer in the solution copolymerization of ethylene

Abstract: SYNOPSISThe copolymerization of ethylene with highly active TiC14/ MgC12-supported catalysts in solution reactors at 185°C and 400 Psig pressure is presented. The performance of these highly active supported catalysts at high reaction temperature is characterized by a high initial rate that decays rapidly within the 10 min polymerization time period. In the presence of hydrogen and a comonomer, catalyst yields up to about 300 kg/g ( T i ) are achieved. Kinetic data obtained on the influence of a comonomer, e.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…The comonomer effect has been shown to be a function of the type, quantity, and chain length of the α‐olefin in question. Studies have shown that at low comonomer concentrations, the rate increases with respect to homopolymerizations for monomers like 1‐hexene or 1‐octene, but then decreases after some optimum concentration added . When polymerization takes place on a supported catalyst, similar trends have been observed, where the rate can become significantly higher than the rate of ethylene homopolymerization for small quantities of α‐olefin, but after an optimal amount, the rate once again decreases and can become even lower than the reference value during homopolymerization .…”
Section: Introductionmentioning
confidence: 76%
“…The comonomer effect has been shown to be a function of the type, quantity, and chain length of the α‐olefin in question. Studies have shown that at low comonomer concentrations, the rate increases with respect to homopolymerizations for monomers like 1‐hexene or 1‐octene, but then decreases after some optimum concentration added . When polymerization takes place on a supported catalyst, similar trends have been observed, where the rate can become significantly higher than the rate of ethylene homopolymerization for small quantities of α‐olefin, but after an optimal amount, the rate once again decreases and can become even lower than the reference value during homopolymerization .…”
Section: Introductionmentioning
confidence: 76%
“…In Ziegler‐Natta olefin polymerization, the enhancement of polymerization rate ( R p ) by the addition of comonomer is well known as the comonomer effect 1. The effect has been widely observed in copolymerization of ethylene with α‐olefins and of propylene with ethylene or the other α‐olefins 7, 11, 24–33. A great deal of effort has been devoted to providing several mechanistic explanations of the comonomer effect.…”
Section: Introductionmentioning
confidence: 99%
“…While maintaining consistency with the hoethylene and 1-hexene over a TiCl 4 /MgCl 2 catamopolymerization results, the parameters of the lyst. The data provided in the work of Jaber and expanded model were then used to match the obRay 31 has been used as the basis for this example, served rate, yield, degree of polymerization, and since it provides the most detail in terms of the comonomer incorporation for the 1-hexene copolyreaction system and conditions used. Furthermerization.…”
Section: Figure 15mentioning
confidence: 99%